Does COVID-19 affect mental health and substance use in young adults? - Duo (Helen); Sreelekha Prakash; Riya Goyal; Rebecca Zhang (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Mental health has been impacted by COVID-19 throughout the United States and beyond. The mental health and well-being were further affected with excessive substance use during the pandemic. The aim of this research was to explore how the COVID-19 affects the mental health of the young adults (18-24 years) in the South Jersey area. We also examined the association between mental health symptoms in young adults and substance use during the first and second year of the pandemic. METHODS AND MATERIAL: A cross-sectional survey was conducted with (n = 711) 527 participants that included young adults (18-24 years old) across university campus in south jersey and in the community cohorts. Multinomial regression analysis and Chi-squared test were used to explore the association between mental symptoms and substance use. Data were analyzed using Microsoft Excel Spreadsheet for descriptive statistics and Python 3.0 scikit-learn package. RESULTS: The study showed that "Lonely" and "Hopeless" were the top two mental health symptoms. It was observed that the symptoms of "Lonely" and "Hopeless" increased for both males and females. In general, males seemed to be affected more than females in this study for mental health symptoms. For substance use, "Nervous" and "Smoking" showed positive correlation in 2020 and "Hopeless" and "Alcohol" were positively correlated in 2021. CONCLUSIONS: Young adults' mental health symptoms and substance use has been proven to be affected through the pandemic and this research results even though localized will assist the community and educational institutions to plan better support to assist young adults with better health and wellness initiatives.